2003
DOI: 10.1046/j.1365-2761.2003.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Melano‐macrophage centres and their role in fish pathology

Abstract: Melano-macrophage centres, also known as macrophage aggregates, are distinctive groupings of pigment-containing cells within the tissues of heterothermic vertebrates. In fish they are normally located in the stroma of the haemopoietic tissue of the spleen and the kidney, although in amphibians and reptiles, and some fish, they are also found in the liver. They may also develop in association with chronic inflammatory lesions elsewhere in the body and during ovarian atresia. In higher teleosts, they often exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
537
1
20

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 708 publications
(589 citation statements)
references
References 57 publications
31
537
1
20
Order By: Relevance
“…Rombout and van den Berg (1989) administered antigens via anal to carp, and registered increased number of macrophages in the distal intestine; the authors also considered the observed, enlarged intraepithelial macrophages morphologically similar to melanomacrophages, thus able to drive local immune response. Melanomacrophages are pigmented macrophages aggregates, ordinarily found in the kidney, liver and spleen of bony fish (Agius and Roberts, 2003;Haugarvoll et al, 2006;Wolke, 1992), or adventitiously to inflamed regions (Koppang et al, 2005;Rodríguez et al, 2005); functions of melanomacrophages are multiple, complex…”
Section: Resultsmentioning
confidence: 99%
“…Rombout and van den Berg (1989) administered antigens via anal to carp, and registered increased number of macrophages in the distal intestine; the authors also considered the observed, enlarged intraepithelial macrophages morphologically similar to melanomacrophages, thus able to drive local immune response. Melanomacrophages are pigmented macrophages aggregates, ordinarily found in the kidney, liver and spleen of bony fish (Agius and Roberts, 2003;Haugarvoll et al, 2006;Wolke, 1992), or adventitiously to inflamed regions (Koppang et al, 2005;Rodríguez et al, 2005); functions of melanomacrophages are multiple, complex…”
Section: Resultsmentioning
confidence: 99%
“…Melanin synthesis is carried out by the tyrosinase family protein and is auto-regulated and activated by its own substrate and cofactor tyrosine (Stearns & Wang, 1987). The process of melanin synthesis usually occurs inside melanophores or melanosomes in the dermis, or in melano-macrophage cells situated in the spleen, kidney and liver (Agius & Roberts, 2003). Therefore, the appearance of melanin inside the eggs of anemonefish is unusual.…”
Section: Discussionmentioning
confidence: 99%
“…Melano-macrophage centers increase in size or frequency in conditions of environmental stress and have been suggested as reliable biomarkers for water quality in terms of both deoxygenation and iatrogenic chemical pollution (Agius & Roberts, 2003).…”
Section: Introductionmentioning
confidence: 99%